Espaço e paisagem jesuítica: perspectivas de análises arqueológicas em Laranjeiras/SE - Santos, Ronaldo José Ferreira Alves (2014)
This dissertation aims to discuss the prospects of archaeological analysis about space and landscape Jesuit in Laranjeiras/SE . While culture of a given society stuff architectural structures and Chapel Mill House Retreat and Church of Our Lady of the Conception of Comandaroba probably built in 1701 and 1734 respectively can inform us details of occupation, use and transformation of the landscape and activities of these sites . The presence of the Jesuits in Sergipe date from the process of colonization in the sixteenth century when they arrived and settled. The overall objective of this dissertation is to analyze from the material culture the information comprising the insertion of the Jesuits in Laranjeiras/SE . Noting the occupation, use and processing that were undertaken in space shaping the landscape generating material culture including social, cultural and economic relations developed by this colonial social group in the region. The understanding of this issue was made possible through the application of theoretical and methodological Space Archaeology, Landscape and Architecture that supported the research. The landscape is as the material result of the interaction between man and the environment in which reflects its practices and relationships.